Digital Creativity Strategies and Work Ethic of Gen Z Entrepreneurs: Case Study of Online Business Students Surakarta, Indonesia - Cahyaning Asari; Suranto Suranto (Advances in Business & Industrial Marketing Research, 2026)
Purpose: This study examines the influence of digital creativity strategies and work ethic on the performance of Gen Z student entrepreneurs in online businesses at Muhammadiyah University of Surakarta (UMS) and Sebelas Maret University (UNS), with a focus on engagement and business sustainability in digital markets. Research Method: A qualitative case study design was applied. Data were collected from 12 purposively selected student entrepreneurs through semi-structured interviews and three-month observations of their activity on Instagram and TikTok. Data were analyzed using the Miles and Huberman model with triangulation for validity. Results and Discussion: Findings show that digital creativity is reflected in trend-based content, storytelling, and short videos, while work ethic is shown through discipline, responsibility, and time management. Both factors jointly enhance engagement and support online business continuity. Implications: The study highlights the importance of integrating digital creativity and the development of a work ethic in higher education to strengthen student entrepreneurship ecosystems. Originality: This research provides empirical evidence on the combined role of digital creativity and work ethic in students' entrepreneurial performance within Indonesia’s digital economy.